The Influence of Brand Awareness, Perception of Quality, and Brand Association on Korean Skincare Brand Equity (Study on Korean Skincare Users in Surabaya) - Adisa Lupita Oktavia; Budi Prabowo (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research is motivated by the need to improve quality and introduce modern marketing techniques, which are strategies to compete and excel in order to increase company profitability and strengthen brand value. The purpose of this study was to examine the effect of brand awareness, perceived quality, and brand association on brand equity of Korean skincare products in Surabaya City. This research uses associative research methods with a quantitative approach, and data is conducted on 100 respondents who use Korean skincare products in Surabaya City. This study uses primary data and sampling techniques using non-probability sampling techniques with a purposive sampling approach. This study shows the results that the f test produces an Fcount value greater than Ftable, namely 92.972> 2.70, with a significance value smaller than 0.05, namely 0.00 (0.00 <0.05) so that it can be stated that H1 is accepted. The t-test produces a tcount value of 0.699 < t table 1.985 for brand awareness, while the tcount for perceived quality is 2.391 > t table 1.985, and the tcount for brand association is 6.133 > t table 1.985. From the t-test results, H2 is rejected, while H3 and H4 are accepted. This study concludes that brand awareness, perceived quality, and brand association simultaneously have a significant influence on brand equity. However, there is a lack of influence of brand awareness on brand equity, partially, while perceived quality and brand association partially have a significant influence on brand equity.